Language Teacher Motivation, Autonomy and Development in East Asia - Kimura, Yuzo.; Yang, Luxin; Kim, Tae-Young.; Nakata, Yoshiyuki (Cham : Springer International Publishing : Imprint: Springer, 2022)
This volume highlights unique features of L2 teachers' motivation, autonomy and career development in Far East counties (including Japan, South Korea and China), using diverse methodological research approaches incorporating both quantitative and qualitative paradigms. While much of current research focuses on students' psychology, this volume looks into EFL teachers' motivation and autonomy. Both discussions of theoretical issues of teacher motivation and autonomy and practical, classroom-based investigations are included and written to appeal to researchers, as well as applied teacher audiences. The theoretical chapters give readers a solid grounding in the issues of interest to the field. The practical chapters offer cutting edge insights and can also serve as templates on which postgraduate and postdoctoral researchers can base future studies. This helps the book to offer a dual service to the research community, addressing both issues of theorization of research and the practice of conducting research investigations.
Chapter1.Introduction( Yuzo Kimura, Luxin Yang and Tae-Young Kim) -- Part 1: Theoretical studies: chapter2. Complexity Theory as a Conceptual Framework for Language Phil Hiver Toward Teacher Autonomy: Encouraging Socially Shared Regulation in the Classroom ( Yoshiyuki Nakata ) -- Chapter3. Shifts of Theoretical Paradigms in Second Language Teacher Education and Development: A Critical Review( Lian Zhang) -- Part 2: Empirical studies L2 Teacher Motivation/Autonomy as Complex Systems: Chapter4. Across the Boundaries of L2 Classrooms in the Far East( Yuzo Kimura) -- Chapter5.Dynamics of South Korean EFL Teachers' Initial Career Motives and Demotivation( Tae-Young Kim and Yongmi Kim) -- Chapter6. Exploring the Impact of Group Lesson Discussions on Beliefs and Practices of Three High School EFL Teachers in China( Luxin Yang) -- Chapter7. EFL Teacher Learning in Japan: Joining a Digital Technology Community of Practice( Keiko Sakui & Neil Cowie ) -- Chapter8. From Darkness to Light: Teacher Immunity and the Emergence of Relatedness with Students ( Richard Sampson) -- Chapter9. Teacher Enthusiasm: The Key to Unlocking Teacher and Student Motivation in the L2 Classrooms in East Asia( Peng DING) -- Chapter10. Learning to Teach English Reading Through True Concept Formation: A Case Study of a Pre-service English Teacher's Professional Development ( Eunju Kim) -- Chapter11. A Case Study of Teacher Autonomy in College English Classrooms(Lina Qian ) -- Chapter12. Concluding Chapter (Magdalena Kubanyiova ). .
Keywords: Education; Teachers-Training of; Language acquisition; Language and languages-Study and teaching; Education; Teaching and Teacher Education; Language Acquisition and Development; Language Education; Language Education